1997
DOI: 10.1007/s001470050064
|View full text |Cite
|
Sign up to set email alerts
|

Renal Responses to exercise in heart and kidney transplant patients

Abstract: There is a lack of information about renal responses in heart and kidney transplant patients after intense physical exercise. Eleven heart and ten kidney transplant recipients, as well as two control groups of healthy subjects, were given a maximum exercise test on a bicycle ergometer. One control group was also given a moderate load corresponding to the peak load of the kidney transplant group. Blood and urine samples were collected before and after exercise and assayed for lactate, creatinine, total protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(17 reference statements)
0
3
1
Order By: Relevance
“…The degree of exercise did influence the range of albuminuria and other urinary proteins 11–13 . In contrast to the previous study by Heathcote et al .…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The degree of exercise did influence the range of albuminuria and other urinary proteins 11–13 . In contrast to the previous study by Heathcote et al .…”
Section: Discussioncontrasting
confidence: 65%
“…The degree of exercise did influence the range of albuminuria and other urinary proteins. [11][12][13] In contrast to the previous study by Heathcote et al we improvised low degree exertion treadmill regimen instead of the Bruce Treadmill Protocol. 14 Heathcote et al 14 have shown that the healthy subjects might have albuminuria above the microalbuminuric threshold in high intensity exertion with the Bruce protocol (maximum 12-15 MET).…”
Section: Discussionmentioning
confidence: 99%
“…We emphasised the importance to accurately evaluate GFR in exercising healthy individuals using both Crn serum concentration and urine Crn output,17 from children20 to seniors 16. Also, we stressed the importance of GFR evaluation in diabetic patients,17 21 heart and kidney transplant recipients22–24 involved in exercise training sessions. Indeed, strenuous exercise induces haemoconcentration, while reducing urine output and postexercise return to basal state is related to a half-time decline of about 1 h 25.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, immediately before the administration of 51 Cr-EDTA, will be collected 6 mL of blood from the antecubital vein for creatinine and urea analysis and also will be collected urine samples for creatinine, urea, and albuminuria analyses. Plasma and urine creatinine will be quantified from the automated alkaline picrate method (Poortmans et al, 1997) and albuminuria from the nephelometric method (Fernandez Fernandez et al, 1998).…”
Section: Methodsmentioning
confidence: 99%